Paediatric cardiac anaesthesia in sickle cell disease : a case series - Janse van Rensburg, P J (Department of Anaesthesia, 2015)
Sickle cell disease (SCD) is the most common inherited haematological disorder, producing a mutation of the haemoglobin molecule known as haemoglobin S (HbS). The presence of HbS in the erythrocyte makes it prone to sickling - a process which may lead to vaso-occlusive injury, haemolysis and a hypercoagulable state. Sickling is precipitated by dehydration, hypoxia, hypothermia, acidosis and low flow states. Over time, multi-organ damage develops with significant morbidity and mortality. Paediatric patients with SCD and congenital heart defects may require anaesthesia for corrective cardiac surgery on cardiopulmonary bypass (CPB). During the perioperative period these high-risk patients may suffer significant complications when exposed to the conditions that favour erythrocyte sickling. This case series details our experience of four paediatric patients with SCD patients who underwent corrective cardiac surgery at Red Cross War Memorial Children’s Hospital. The pathophysiology is discussed and the perioperative management of transfusion, cardiopulmonary bypass and temperature regulation is highlighted.